2019
DOI: 10.1111/1365-2664.13508
|View full text |Cite
|
Sign up to set email alerts
|

Increased soil temperature and decreased precipitation during early life stages constrain grass seedling recruitment in cold desert restoration

Abstract: 1. Seed-based restoration is one of the most difficult challenges for dryland restoration. Identifying environmental conditions that drive variation in seed and seedling mortality across similar restoration efforts could increase understanding of when and where restoration outcomes are likely to be favourable and identify new tools and strategies to improve outcomes.2. We asked how variation in a suite of environmental predictors influenced germination, emergence, seedling establishment and juvenile survival o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
53
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 52 publications
(65 citation statements)
references
References 40 publications
10
53
2
Order By: Relevance
“…Although we assessed sagebrush occupancy years later, our data suggest that initial sagebrush germination and emergence success is dictated by daily water availability and temperatures of soil in the first March postfire. Our results are similar to those of James et al (2019), who found increased soil temperatures reduce the establishment of seedlings in the Great Basin ( figure 3). Similarly, James et al (2019) and Young et al (2019) also did not find a correlation between a climatic drought variable, monthly climatic water deficit (CWD = potential evapotranspiration/actual evapotranspiration), and seedling establishment (figure 2).…”
Section: Discussionsupporting
confidence: 92%
“…Although we assessed sagebrush occupancy years later, our data suggest that initial sagebrush germination and emergence success is dictated by daily water availability and temperatures of soil in the first March postfire. Our results are similar to those of James et al (2019), who found increased soil temperatures reduce the establishment of seedlings in the Great Basin ( figure 3). Similarly, James et al (2019) and Young et al (2019) also did not find a correlation between a climatic drought variable, monthly climatic water deficit (CWD = potential evapotranspiration/actual evapotranspiration), and seedling establishment (figure 2).…”
Section: Discussionsupporting
confidence: 92%
“…Together with studies showing monsoonal precipitation largely controls perennial plant recruitment in the southwestern US (e.g. Peters, Herrick, Monger, & Huang, 2010), this suggests outcomes of seeding in drylands will likely be affected by deviations in precipitation in the future (Pascale et al, 2017) and that restoration efforts should be prioritized when seasonal and subā€seasonal forecasts predict average or aboveā€average precipitation (James et al, 2019). These deviations likely overwhelmed siteā€level differences in mean annual precipitation in the wet year of our study, though mesic sites may prove more successful in dry to average years of precipitation.…”
Section: Discussionmentioning
confidence: 76%
“…However, since warmer, drier conditions are forecasted for the study region (Seager et al, 2007), species established from warmerā€adapted seed mixes may have longerā€term potential to persist under future climate conditions. These recruitment trends indicate the importance of climate in determining restoration outcomes and suggest aligning restoration plant niche information with forecasted environmental conditions could be an important tool for increasing seeding success in drylands (Butterfield et al, 2016; James et al, 2019). Projections of seasonal and subā€seasonal conditions are increasingly incorporated into land management and adaptive restoration decisionā€making (Bradford, Betancourt, Butterfield, Munson, & Wood, 2018), and can allow managers to adjust the timing and strategies of management actions such as restoration seed mix species selection to optimize the likelihood of success, given projected conditions (Sitters, Holmgren, Stoorvogel, & LĆ³pez, 2012).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite generally higher seed production per plant on southā€facing slopes, the lower survival of small plants means that higher recruitment rates are likely needed for the southā€facing populations to remain stable. This may have major implications for population persistence in the face of climate change given that in semiā€arid ecosystems recruitment may be particularly sensitive to increasing temperature and aridity (e.g., James et al 2019). Although we expect temperature and moisture to be important direct drivers of demographic process, other differences between slopes, such as the degree of competition with invasive annuals, may have also contributed to the divergent demographic patterns we observed.…”
Section: Discussionmentioning
confidence: 99%